Study on Loan Default Pattern and Auction Cases with Special Reference to Nabil Bank Limited, Global IME Bank Limited, and NIC Asia Bank Limited, Nepal - Trital, Avishek; Dahal, Khet Raj; Parajuli, Ramesh (International Journal on Engineering Technology, 2025)
Loan in banks are highly susceptible of being default during the loan period due to factors such as political instability, poor financial management and others. Among these factors, loan default not only influence the financial situation of the bank itself but also the country as a whole.  This study aims to investigate the causes, consequences, and potential remedies for loan default and its process of auction in Nepal, with Global IME Bank Limited, NIC Asia Bank Limited and Nabil Bank Limited as case studies. The research employed structured questionnaires as the primary data collection tool, with responses from 103 participants and the period of study is carried over a span of a year Analysis revealed that the real estate has the highest number of loan defaults among banks and poor business management among borrowers is the primary reason for loan default. Also during the auction process, the respondents claimed that valuation disputes is the major issue.  The respondents also suggested that quick legal guidelines should be followed in a step-by-step process in order to deal with auction after loan default and also they suggested that ensuring that the loan is used for the proper purpose could also be an effective method to mitigate the defaulted. The study further identified that the most significant consequence of loan default is impact to country’s economy, apart from the bank financial situation.